INTERTEKSTUALITAS AL-QUR’ĀN DENGAN SASTRA DAERAH NUSANTARA: PENDEKATAN LINGUISTIK DAN BUDAYA SASTRA RIAU - M. Zaki Juliansyah; M. Fahrurrozi; Tulus Fiqram Hamawi; Ali Akbar (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to deeply examine the intertextual relationship between the Qur'an and Nusantara regional literature, specifically within the cultural and literary context of Riau Malay, which adheres to the philosophy of “Adat Bersandikan Syarak, Syarak Bersandikan Kitabullah” (Customs based on Islamic Law, Islamic Law based on the Qur'an). The Qur'an, as the source of Islamic teachings, has a widespread transformative influence on Muslim civilization, including in language and literary aspects (in line with Surah Ibrahim [14]: 4), and the principle of diversity for mutual acquaintance (Surah Al-Hujurat [49]: 13). Employing a linguistic and intertextual analysis approach, this research reveals how Qur'anic values, linguistic structures, religious symbolism, and moral and spiritual concepts are absorbed, interpreted, and adapted into Riau Malay literary expressions. The findings indicate that the Islamization process in Riau was not merely theological and social but also strongly impacted the cultural transformation and aesthetics of its literature. Universal Islamic values underwent an assimilation process with local Malay wisdom (Surah Al-A‘rāf [7]: 199), resulting in harmonious literary works. Through Riau Malay pantun, gurindam, hikayat, and syair, it is evident how Qur'anic moral messages are subtly conveyed through characteristic stylistic language, narrative structures, and cultural symbols (Surah Al-Hijr [15]: 9). This study confirms the Qur'an's crucial role as the spiritual and aesthetic foundation that shapes the unique identity of Riau Malay literature.